2016
DOI: 10.1002/mc.22453
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number in whole blood and glioma risk: A case control study

Abstract: Alterations in mitochondrial DNA (mtDNA) copy number are observed in human gliomas. However, whether variations in mtDNA copy number in whole blood play any role in glioma carcinogenesis is still largely unknown. In current study with 395 glioma patients and 425 healthy controls, we intended to investigate the association between mtDNA copy number in whole blood and glioma risk. Overall, we found that levels of mtDNA copy number were significantly higher in glioma cases than healthy controls (mean: 1.48 vs. 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…Our analysis included 36 studies that focused on diverse cancer types from different origins around the world 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 . To reduce the uncertainty induced by confusing factors in the meta-analysis, we evaluated the association between mtDNA content with cancer risk in an overall analysis, as well as stratified analyses by cancer types, genders, ages, ethnicity and life styles.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis included 36 studies that focused on diverse cancer types from different origins around the world 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 . To reduce the uncertainty induced by confusing factors in the meta-analysis, we evaluated the association between mtDNA content with cancer risk in an overall analysis, as well as stratified analyses by cancer types, genders, ages, ethnicity and life styles.…”
Section: Discussionmentioning
confidence: 99%
“…For this case-control study, glioma patients were recruited from The University of Texas MD Anderson Cancer Center (Houston, TX). Detailed information on these cases has been reported previously [ 34 ]. All patients with either newly diagnosed or previously treated histopathologically confirmed glioma who were registered at MD Anderson between April 2014 and July 2016 were eligible for our study.…”
Section: Methodsmentioning
confidence: 99%
“…In previous years, numerous retrospective and prospective studies have demonstrated a powerful association between increased peripheral blood mtDNA copy number and the risk of different types of cancer (6,7,(20)(21)(22)(23)(24). However, the link between blood mtDNA and carcinogenesis is not fully explained.…”
Section: Discussionmentioning
confidence: 99%